Modelo de apuração de custos para a Universidade Federal do Tocantins: uma ferramenta de apoio à gestão - Trombini, Michelle Matilde Semiguen Lima (Universidade Federal do Tocantins, 2015)
The Management of Federal Universities, because they are complex organizations and of public responsibility, has become increasingly challenging, which leads to the need of promoting its improvement to ensure the monitoring of the factors that influence the fulfillment of the mission and institutional goals. In this context, this paper seeks to contribute to the managers of the Universities for being an instrument that can be used as a tool in the decision-making process. Through the proposition of cost calculation model, the Federal University of Tocantins can monitor its costs in order to make safe decisions, so this model may also contribute indirectly to the guarantee of quality education. In this context, this research aims to propose a cost calculation model for the Federal University of Tocantins. The model was based on the Activity-Based Cost (ABC) for the generation of information as a tool to support management. ABC cost calculation technique provides for the monitoring of the activities that entailed higher costs, and these costs were allocated to products, enabling thus the analysis of costs in two views: vertical viewing - for allocation of costs to cost objects through the activities carried out; and the horizontal or processes viewing - to capture the costs of processes through the activities carried out. The ABC method, besides allowing the management of resources, also allows the identification and management of the relevant activities to achieve its objectives and scope of the institutional mission.